Defining the Federal and State Realms of Tender Offer Regulation - Robert B. Thompson (Washington University Law Quarterly, 1986)
This Article analyzes the appropriate roles of federal and state law in regulating tender offers by first identifying the incomplete view of federal-state relations found in current case law. Subsequent sections detail the methods by which states now seek to regulate takeovers and the degree to which these state methods are consistent with federal law.
Keywords: Tender offers (Securities); Blue sky laws